2018
DOI: 10.1136/bmjqs-2017-007359
|View full text |Cite
|
Sign up to set email alerts
|

Pilot randomised controlled trial to improve hand hygiene through mindful moments

Abstract: BackgroundTo evaluate the effectiveness of a brief mindfulness intervention on hand hygiene performance and mindful attention for inpatient physician teams.DesignA pilot, pre-test/post-test randomised controlled mixed methods trial.SettingOne academic medical centre in the USA.ParticipantsFour internal medicine physician teams consisting of one attending, one resident, two to three interns and up to four medical students.InterventionA facilitated, group-based educational discussion on how mindfulness, as pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Scores for the quality of the studies ranged between 6.5 and 14.5 on the MERSQI scale; the mean score was 9.9, reflecting average quality (Table S2) . The eligible studies included seven randomised controlled trials (RCTs), three non‐randomised controlled trials (CTs), 12 pre‐post studies, and two qualitative interview studies (Table ). Of the RCTs and CTs, four studies employed a waitlist control condition, four studies employed a passive control condition, and two studies exposed controls to protected free time during the intervention period .…”
Section: Resultsmentioning
confidence: 99%
“…Scores for the quality of the studies ranged between 6.5 and 14.5 on the MERSQI scale; the mean score was 9.9, reflecting average quality (Table S2) . The eligible studies included seven randomised controlled trials (RCTs), three non‐randomised controlled trials (CTs), 12 pre‐post studies, and two qualitative interview studies (Table ). Of the RCTs and CTs, four studies employed a waitlist control condition, four studies employed a passive control condition, and two studies exposed controls to protected free time during the intervention period .…”
Section: Resultsmentioning
confidence: 99%
“…A recent empirical study [29] has shown that physicians practice hand hygiene in their daily work more frequently after a one-hour mindfulness-intervention. The focus of this intervention was neither specialized subject knowledge nor particular abilities, but more consciousness and presence in the daily work.…”
Section: Hygiene As a Professional Competence Of Clinical Staffmentioning
confidence: 99%
“…Besides, communication seminars for employees can also be beneficial – especially when they aim at maintaining hygiene rules within the team (nursing staff, therapists, physicians, [42]). Furthermore, increased attention promotes hygiene competence, for example implemented through evaluations, mentoring, feedback, institution-internal and national/international campaigns [1], [41]) or awareness-focused programs [29]. A further aspect important in this respect are role-models, who influence young clinicians in their behavior [30], [31], [43], [44].…”
Section: Further Development Of the Model Of Hygiene Competence And Cmentioning
confidence: 99%
“…In pandemics like COVID-19 in the year 2020, the prevention of infection through good hygiene is crucial. Some pre-existing forms of intervention are designed to increase awareness and improve attitudes towards hygiene in daily clinical work [3][4][5].…”
Section: Introductionmentioning
confidence: 99%